2019
DOI: 10.1111/cas.13944
|View full text |Cite
|
Sign up to set email alerts
|

Distinct chemotherapy‐associated anti‐cancer immunity by myeloid cells inhibition in murine pancreatic cancer models

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a lethal malignancy associated with an extremely poor prognosis. Chemotherapy, such as gemcitabine (GEM), is the only treatment for PDAC patients who are not suitable for radical surgical treatment; however, its anti‐tumor efficacy is limited. In this study, we investigated the host immune system response in murine PDAC models undergoing GEM treatment. We found that PDAC tumor tissues were infiltrated with a substantial number of Gr‐1+ myeloid cells and had relatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Previously, we observed changes of the host immune response by GEM treatment; specifically, there was a decreased number of MDSCs in tumor tissues and peripheral blood, an increase in the frequency of CD4+ and CD8+ T cells, and enhanced functional activity of CD8+ T cells for killing tumor cells. 8 We also observed that the tumors of PDAC mice treated with GEM showed an increase in PD-1 expression, which was abolished by anti-PD-1 Ab treatment (online supplemental figure S2). Thus, GEM plus anti-PD-1 Ab treatment enhanced the anticancer immune effect compared with single GEM treatment.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Previously, we observed changes of the host immune response by GEM treatment; specifically, there was a decreased number of MDSCs in tumor tissues and peripheral blood, an increase in the frequency of CD4+ and CD8+ T cells, and enhanced functional activity of CD8+ T cells for killing tumor cells. 8 We also observed that the tumors of PDAC mice treated with GEM showed an increase in PD-1 expression, which was abolished by anti-PD-1 Ab treatment (online supplemental figure S2). Thus, GEM plus anti-PD-1 Ab treatment enhanced the anticancer immune effect compared with single GEM treatment.…”
Section: Discussionmentioning
confidence: 68%
“…19 We previously reported that MDSCs potentially diminished the effect of GEM treatment, and the ablation of myeloid-derived cells augmented the anti-cancer effect of GEM, which was mediated by CD8+ T cells. 8 From the current results, anti-PD-1 Ab treatment appears to be a promising choice as a combinatorial agent for PDAC chemotherapy. Macrophages are reportedly affected by anti-PD-1 Ab treatment 20 or can be directed toward M1 macrophages in the PD-1 knock-out condition.…”
Section: Discussionmentioning
confidence: 92%
“…Depletion of myeloid-lineage cells enhanced anti-cancer immunity associated with gemcitabine (GEM) treatment in mice with pancreatic ductal adenocarcinoma (PDAC) tumors (65). GEM is a nucleoside analog used as first-line treatment.…”
Section: Tamcs In Conventional Chemotherapy and Targeted Therapy Negamentioning
confidence: 99%
“…Following GEM treatment, myeloid cells in tumor tissues and in peripheral blood decreased while numbers of CD4 + or CD8 + cells increased suggesting that anti-cancer immunity was enhanced. In addition, concurrent treatment of mice with GEM and further depletion of myeloid cells using an anti-GR-1 antibody significantly prolonged survival (65). Inflammatory breast cancer (IBC) is often characterized by overexpression of epidermal growth factor receptors 1 and/or 2 (ErbB1, ErbB2) that activate downstream survival pathways phosphatidylinositol-3-kinase (PI3K)/protein kinase B (AKT) and MAPK (66).…”
Section: Tamcs In Conventional Chemotherapy and Targeted Therapy Negamentioning
confidence: 99%
“…These antibodies bind to the pathogens and thus marking them to be attacked by the innate cells. In addition, it is worthwhile to mention that some of the oncology patients are undergoing chemotherapy treatment which affects their immune system cells causing a severe reduction in the leukocytes count [26]. In case of intracellular pathogens, the role of CD + 8 T-cells, which are stimulated by CD + 4 T-cells, is to kill the host cells that harbor foreign molecules (such as for a virus).…”
mentioning
confidence: 99%